The Definition of Disability in (German and) International Discrimination Law - Theresia Degener (Disability Studies Quarterly, 2006)
This paper is about the issue of defining disability in the context of discrimination law. It reviews the definition of disability in the German disability discrimination laws, the Act on the Equalization of Disabled Persons (Behindertengleichstellungsgesetz, BGG) of 2002 and the new German rehabilitation law which is encapsulated in the Ninth Book of the Social Law Code (Sozialgesetzbuch, Neuntes Buch, SGB IX) of 2001. The main question of this review is whether the respective definitions of disability perpetuate the medical/individual model of disability, or support the social model/human rights model of disability. According to the medical/individual model of disability the problems disabled persons face in their daily life are mainly caused by their impairment, whereas the social/human rights model locates the problems in societal and environmental barriers outside the individual disabled person. The German disability definition is analyzed and evaluated in comparison to a number of selected countries around the world.
Keywords: Disability definitions; discrimination law; Germany; medical and social models